PENGARUH MANAJEMEN KONFLIK TERHADAP KINERJA PEGAWAI DI KANTOR CAMAT ONOHAZUMBA KABUPATEN NIAS SELATAN - Nurhayati Waruwu (LPPM Universitas Nias Raya, 2022)
The problem of this research is the quantity and quality of employee performance is not in accordance with what is targeted such as the completion of work in 3 days but it has only been completed in 7 to 8 days and there are often work mismathches such as in carrying out work such as 10 of these targets there were four that were not appropriate or incorrect. The purpose of this study was to determine the affect of conflict management on employee performance in Onohazumba Sub-District, South District. The type of research used is a quatitative associative reseacht type. Data sources are 30 employees. Collection techniques by distributing questionnaires or questionnaires. The data analysis method used is simple linear regresiossion analysis. Based on a simple linear regressionthe equation of the bo coefficient as a contant (fixed value) the value of 14.999 is the value of the coefficient of the coefficient of the Conflict Management varable β1 of 0.734 this value means that every increase in the conflict management variable (X) by unit will increase variable employees (Y) of 0.734. the results of this study indicate that the tvalue of conflict management is>5.732 ttable of 1.701. this study can be concluded tha there is an influence of conflict management on the performance of Onohazumba employees in south Nias District. The sarong in this study is to improve the performance of the leadership employees as well as a whip at the Onohazumba Sub-District Office, south Nias District, must really continue to improve conflict management even better and pay attention to it. Conflict management that has a major influence on employee performance.